Ramsey's legacy - Lillehammer, Hallvard, 1970-; Mellor, D. H. (Mind Association occasional series., 2005)
The Cambridge philosopher Frank Ramsey died tragically in 1930 at the age of 26, but had already established himself as one of the most brilliant minds of the twentieth century. Besides groundbreaking work in philosophy, particularly in logic, language, and metaphysics, he created modern decision theory and made substantial contributions to mathematics and economics. In these original essays, written to commemorate the centenary of Ramsey's birth, a distinguished international team. of contributors offer fresh perspectives on his work and show its ongoing relevance to present-day concerns.